E-216 Stroke thrombectomy outcomes by biological sex – a multicenter study from the star collaboration. (23rd July 2022) - Dimisko, L; Hertzberg, V; Grossberg, J; Howard, B; Cawley, C; Tong, F; Jabbour, P; Maier, I; Wolfe, S; Rai, A; Starke, R; Gory, B; et al.
Abstract : Background: Female gender has been associated with worse clinical outcomes after ischemic stroke and account for the majority of stroke mortality. Females were more likely to receive intra-arterial therapy for ischemic stroke but had worse clinical outcomes then their male counterparts. Data on gender differences in endovascular thrombectomy remains limited. Methods: We analyzed gender-specific outcomes from the prospectively maintained Stroke Thrombectomy and Aneurysm Registry (STAR). We included adult patients undergoing endovascular thrombectomy for acute ischemic stroke from 32 centers in the US and globally between January 2015 and May 2021. Patient demographics, baseline deficits, admission variables, technical and clinical outcomes were reviewed and compared between the males and females. The primary outcome measure was modified Rankin Score (mRS) at 90 days dichotomized into good outcome (mRS 0–2) and poor outcome (mRS 3–6). Results: A total of 7477 patients were included in the study of which 50% were females. On average, female patients were older (70 vs. 67, p< 0.01), more likely to have comorbid atrial fibrillation (39% vs. 34%, p< 0.01), and more likely to have mRS > 2 on presentation (11% vs. 8%, p<0.01). However, there was no difference in admission NIHSS, admission ASPECT scores, onset-to-groin time, and use of bridging thrombolysis between the two groups. On univariate analysis, females had significantly higher mRS score at 90-days compared to males (p<0.01) and demonstrated lower rates of functional independence (mRS 0–2, 34% vs. 40%, p<0.01). Using propensity score matching, when controlling for baseline covariates, there was no significant difference in 90-day mRS scores between males and females. Similarly, when baseline covariates were controlled for on univariate analysis, there was no significant gender differences in 90-mRS scores or procedural complications. Predictors of good functional outcome at 90 days were similar in males and females. Conclusions: Older females with higher baseline disability are more likely to undergo mechanical thrombectomy compared to males. Biological sex is not an independent predictor of thrombectomy outcomes in acute stroke when controlling for baseline and comorbid variables. Future studies will explore the determinants underlying differences in presentations and outcomes between Disclosures: L. Dimisko: 1; C; T32NR012715. V. Hertzberg: None. J. Grossberg: None. B. Howard: None. C. Cawley: None. F. Tong: None. P. Jabbour: 2; C; Medtronic, MicroVention, Cerus Endovascular, and Balt. I. Maier: None. S. Wolfe: None. A. Rai: None. R. Starke: 1; C; Medtronic, NREF, Joe Niekro Foundation, Brain Aneurysm Foundation, Bee Foundation, and by National Institute of Health(R01NS111119–01A1) and(UL1TR002736, KL2TR002737) through the Miami Clinical and Translational. 2; C; xPenumbra, Abbott, Medtronic, InNeuroCo and Cerenovus. B. Gory: None. M. Psychogios: 1; C; Phenox, Stryker, and Siemen.. A. Shaban: None. A. Arthur: 1; C; Cerenovus, MicroVention, Penumbra, and Siemens. 2; C; Balt, Johnson and Johnson, Leica, Medtronic, MicroVention, Penumbra, Scientia, Siemens, and Stryker. 4; C; Bendit, Cerebrotech, Endostream, Magneto, Marblehead, Neurogami, Serenity, Synchron, Triad Medical, and Vascular Simulations. J. Kim: None. S. Yoshimura: None. P. Kan: 2; C; Stryker and Cerenovus. R. De Leacy: None. I. Fragata: None. A. Polifka: None. J. Osbun: None. T. Dumont: None. R. Williamson: None. R. Crosa: None. M. Levitt: None. M. Moss: None. M. Park: None. W. Casagrande: None. S. Chowdhry: None. A. Spiotta: 1; C; Penumbra, Pulsar Vascular, MicroVention, and Stryker. 2; C; Penumbra, MicroVention, and PulsarVascular;. A. Alawieh: None.